Effect on the reduction of bacterial load after surgical hand antisepsis with triclosan 0.5% compared to triclosan 0.5% followed by 70% alcoholic solution. (22nd March 2023) - Santé, Luis; Gómez-Lus, María Luisa; Martin-Villa, Carlos; Becerro-de-Bengoa-Vallejo, Ricardo; Alou, Luis; Sevillano, David
Abstract: Triclosan 0.5% by scrubbing does not meet the UNE-EN12791 criteria to be used in the surgical hand preparation (SHP). Triclosan 0.5% by scrubbing followed by ethanol 70% hand rubbing is suitable without the additional characteristic of sustained effect. This limited effectiveness implies that triclosan should be avoided in SHP given the restrictions on its use in consumer antiseptic products. The trial was registered at ClinicalTrials.gov (ID: NCT04538365).